The frequency of breakfast consumption between males and females among sports science undergraduates / Mohamad Hisyam Izzuddin Mohamed Ishak and Razali Mohammed Salleh - Mohamed Ishak, Mohamad Hisyam Izzuddin; Mohammed Salleh, Razali (Faculty of Sports Science and Recreation, University Press of Universiti Teknologi MARA, 2020)
Human health depends on regular practice of healthy lifestyles which included a balanced diet that consist of a variety of important nutrients in the food. Creating a balanced diet and regular eating habits were the basis of the positive changes in our eating habits and it was also as the source of our recovery. Breakfast had been the most important meal of the day. However, there were still evidences of individuals who skip breakfast. The purpose of this study was to determine the frequency of breakfast consumption between male and female among sports science under graduates. A total of 50 undergraduates participated in this study. Result of the study showed 66% of sports science undergraduates took breakfast while 34% of them were classified as breakfast skippers. Male were frequently taking breakfast (72%) as compared to female students (60%) (p < .05). In conclusion, sports science study promotes awareness on healthy lifestyle apart from sports and breakfast was one of the factors. Extra work to spread the health awareness to the people could be significant for illuminating a better lifestyle.